STUDENT STRATEGIES AND ERRORS IN SOLVING MATHEMATICAL REPRESENTATION PROBLEMS ON A QUADRATIC FUNCTION MATERIAL - Hesty Marwani Siregar; Nurjanah Nurjanah; Turmudi Turmudi; Darhim Darhim; Elah Nurlaelah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
Students often experience difficulties in using multiple mathematical representations when solving quadratic function problems, particularly in connecting visual, symbolic, and verbal forms. While previous studies have mainly focused on identifying students’ errors, the strategies underlying these errors remain insufficiently explored. This study aims to identify the students’ strategies when solving mathematical representation problems on quadratic functions material. Using a descriptive qualitative approach, written responses from 127 students at two public high schools in Pekanbaru were analyzed and supported by interviews with six selected students to clarify their reasoning. The findings show that students predominantly relied on procedural strategies, such as point substitution or mechanical formula use, with limited conceptual understanding. Although most students attempted the visual task, many produced inaccurate graphs. The symbolic and verbal indicators showed very high non-response rates, indicating difficulties in translating contextual information into algebraic form and expressing mathematical reasoning. These results highlight the need for instructional approaches that integrate multiple representations and strengthen conceptual connections.